Designing a Predictive Model Using Artificial Intelligence to Evaluate Training Load in Football Players - Ali, Ali Hussein; A. Shalal , Azhaar (Indonesian Journal Publisher, 2025)
The objective of this research is the development of a predictive model using artificial intelligence techniques that makes it possible to evaluate the training load presented by soccer players, with the intention to optimize training programs and ensuring that they are in line with players' capabilities and physiological and physical needs. The model was built using a diverse set of sports and physiological data observed by modern tools utilising high-end technological capabilities. This study centred around designing algorithms that are able to learn from past and present data to predict whether athletes will respond in certain ways to prescribed training loads, therefore supporting more precise and efficient coaching decisions. In addition to supporting the previously studied approaches based on conventional approaches, the proposed model has been shown by us to be more easily adaptable and accurate in evaluation, with a much higher degree of flexibility, enabling it quickly to handle and analyze large volumes of data reliably. The findings from the analysis indicated a great potential for the best use of artificial intelligence within this domain to improve sports performance and mitigate the likelihood of injuries/unstructured training. The success of the model will mainly rely on data quality, which in this case focused on obtaining data from a range of different devices (performance measurement devices, imaging technologies, and biological analysis techniques) to accurately depict each player's physical status [20, 22]. This model helps in delivering the sophisticated analytical tools that enable coaches to continuously monitor training load, and build player-specific training schedule to create a fine balance between load and recovery. ConclusionOverall, this work is among the first steps towards incorporating artificial intelligence into sports development pathways, but also opens up future perspectives that will be characterized by exponential technological progress and will be driven to leverage improvement evaluation and training programme management processes in a more efficient and precise manner.